Contemporary Persian Gulf essays in honour of Gulshan Dietl, Prakash Chandra Jain and Girijesh Pant - Dietl, Gulshan; Jain, Prakash C. (Prakash Chand) 1946-; Kumaraswamy, P. R.; Pant, Girijesh; Quamar, Md. Muddassir (KW Publishers Pvt Ltd., 2016)
1. Introduction-- 2. Investment in Renewable Energy in the GCC States-- 3. Transition to a Green Economy-- 4. Trajectories of Education Policy in Saudi Arabia --5. Shiism, Rentier State and Illiberal Democracy in Iran-- 6. Sectarianism, Geopolitical Rivalry and the Syrian Civil War --7. The Widening Gulf-- 8. Qatar-Hamas Relations-- 9. India - GCC FTA --10. Thicker than Oil